IMMUNOLOGICAL FACTORS IN TRANSPLANTATION - Ismoilov Ibodjon Imomjonovich (Journal of new century innovations, 2023)
Abstract. Compared to transplantation of other organs, such a direction as kidney transplantation has more than half a century of history. During this period, tremendous experience has been accumulated regarding the modernization of surgical techniques, organ preservation, improvement and optimization of immunosuppression protocols, as well as postoperative management of patients. By the end of the 90s, modern survival rates for renal transplants and recipients had been achieved. The success of kidney transplantation, however, has led to the fact that "waiting lists" for the operation are growing steadily every year around the world.